2021
DOI: 10.1136/bmjgast-2020-000573
|View full text |Cite
|
Sign up to set email alerts
|

Risk of common infections in people with inflammatory bowel disease in primary care: a population-based cohort study

Abstract: ObjectiveTo evaluate the risk of common infections in individuals with inflammatory bowel disease (IBD) [ulcerative colitis and Crohn’s disease] compared with matched controls in a contemporary UK primary care population.DesignMatched cohort analysis (2014–2019) using the Royal College of General Practitioners Research and Surveillance Centre primary care database. Risk of common infections, viral infections and gastrointestinal infections (including a subset of culture-confirmed infections), and predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 59 publications
5
37
0
Order By: Relevance
“…However, these enteric infections did not impact IBD outcomes ( Axelrad et al, 2018 ). A recent study from UK also reported that patients with IBD in primary care were more likely to present with common infections including gastrointestinal infections of C. difficile , Salmonella , Shigella and Campylobacter ( Irving et al, 2021 ). Campylobacter species isolated in diagnostic laboratories are mainly Campylobacter jejuni .…”
Section: Bacterial Species Associated With Human Inflammatory Bowel D...mentioning
confidence: 99%
“…However, these enteric infections did not impact IBD outcomes ( Axelrad et al, 2018 ). A recent study from UK also reported that patients with IBD in primary care were more likely to present with common infections including gastrointestinal infections of C. difficile , Salmonella , Shigella and Campylobacter ( Irving et al, 2021 ). Campylobacter species isolated in diagnostic laboratories are mainly Campylobacter jejuni .…”
Section: Bacterial Species Associated With Human Inflammatory Bowel D...mentioning
confidence: 99%
“…The etiology of IBD is multifactorial, including the contribution of genetic, environmental, host factors and their reciprocal interactions ( Flynn and Eisenstein, 2019 ); recent data indicate a worldwide 0.3% incidence and prevalence of IBD ( Ng et al, 2017 ). The therapeutic treatment of IBD with immunomodulators ( Park et al, 2020 ) and biologics ( Neurath, 2019 ) may activate a transient or persistent immunocompromised state inducing opportunistic infections, especially when multiple drugs are prescribed simultaneously ( Bonovas et al, 2016 ; Shah et al, 2017 ; Irving et al, 2021 ). Several research groups investigated whether patients with IBD may be or not more susceptible to developing SARS-CoV-2 infection ( Monteleone and Ardizzone, 2020 ), how they should be managed in the context of the COVID-19 pandemic, and the risks and benefits of the therapeutic treatment with immunomodulators, especially in the pediatric age ( Dipasquale et al, 2020 ; Sultan et al, 2020 ).…”
Section: Sars-cov-2 Infection In Patients With Ibdmentioning
confidence: 99%
“…To evaluate the risk of common infections in individuals with (IBD) 18 829 people with IBD were matched to 73 316 controls. Authors found that the patients with IBD were more likely to present to primary care with a common infection over the study period (46% vs 37% of controls) ( Irving et al, 2021 ) [M]. Moreover, the risks of infections, was higher in patients who were treated with oral glucocorticoid therapy, but not with aminosalicylates.…”
Section: Systemic Glucocorticoids [Sed-15 906; Seda-33 841; Seda-34 653; Seda-35 719; Seda-36 604; Seda-37 492; Seda-38 425 Seda-42]mentioning
confidence: 99%